2010
DOI: 10.1017/s0950268810001949
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster in Australia: evidence of increase in incidence in adults attributable to varicella immunization?

Abstract: Rates of herpes zoster (HZ) hospitalizations, antiviral prescriptions, and New South Wales emergency-department presentations for age groups <20, 20-39, 40-59 and ⩾60 years were investigated. Trends were analysed using Poisson regression to determine if rates increased following funding of varicella immunization in Australia in November 2005. The regression analysis revealed significantly increasing trends of between 2% and 6% per year in both antiviral prescriptions and emergency-department presentations in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 37 publications
5
32
0
1
Order By: Relevance
“…[30][31][32] Some epidemiological studies have reported temporal increases in the crude HZ hospitalization rates. 19,33 However, only two other studies have assessed trends in age-standardized HZ rates before and after vaccine introduction, including hospitalizations and health care utilization, and showed no temporal increase in HZ (Table 5). 35,36 Increasing age is the greatest risk factor for VZV reactivation, due to agerelated decline in cellular immunity, high prevalence of chronic disease and use of immune-compromising medication.…”
Section: Varicella Vaccination and Admissions To Hospitals In Australiamentioning
confidence: 99%
“…[30][31][32] Some epidemiological studies have reported temporal increases in the crude HZ hospitalization rates. 19,33 However, only two other studies have assessed trends in age-standardized HZ rates before and after vaccine introduction, including hospitalizations and health care utilization, and showed no temporal increase in HZ (Table 5). 35,36 Increasing age is the greatest risk factor for VZV reactivation, due to agerelated decline in cellular immunity, high prevalence of chronic disease and use of immune-compromising medication.…”
Section: Varicella Vaccination and Admissions To Hospitals In Australiamentioning
confidence: 99%
“…Other studies have found an increasing incidence of HZ in the United States and other countries, consistent with our findings. 2,[18][19][20][21] The cause for this elevation in disease burden is unclear and is likely multifactorial. The age-specific increased rate of HZ-related ED visits in patients aged 20 to 59 years may be explained in part by the Hope-Simpson hypothesis that increased varicella zoster virus vaccination has led to a rise in overall HZ incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Although the deputising service data reported here indicate variability in zoster consultations, we have described a clear increasing trend in presentations for zoster in community patients younger than 70 years, and found some indication of a decreased number of consultations for zoster in the community among those aged 80 years and older. A mixed picture of age-related changes in zoster has been reported from various data sources in various countries [18,19,27,28]. However, compared with many other countries, Australia has relatively high childhood varicella vaccine coverage, which may impact on zoster, as well as varicella, incidence.…”
Section: Discussionmentioning
confidence: 99%